2021
DOI: 10.1161/atvbaha.120.315747
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Atherosclerosis in Predicting Coronary Artery Disease

Abstract: Objective: This meta-analysis aims to compare the relationship between phenotypic manifestation of coronary and carotid atherosclerosis using available imaging techniques. Approach and Results: We searched all electronic databases until October 2020 for studies which reported relationship between carotid and coronary atherosclerosis. The primary end point was correlation between carotid intima-media thickness (CIMT) and carotid plaque fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 106 publications
1
38
0
Order By: Relevance
“…The carotid and coronary arteries are the two most common systems afflicted by atherosclerosis. Despite the different anatomical locations, the two artery systems have been suggested to share a similar phenotypic pattern of atherosclerosis in plaque formation, luminal narrowing or obstruction, and arterial wall calcification ( 50 ). Therefore, the hub genes derived from carotid atherosclerosis deterioration may be related to the acute clinical phenotype of coronary plaques such as MI.…”
Section: Discussionmentioning
confidence: 99%
“…The carotid and coronary arteries are the two most common systems afflicted by atherosclerosis. Despite the different anatomical locations, the two artery systems have been suggested to share a similar phenotypic pattern of atherosclerosis in plaque formation, luminal narrowing or obstruction, and arterial wall calcification ( 50 ). Therefore, the hub genes derived from carotid atherosclerosis deterioration may be related to the acute clinical phenotype of coronary plaques such as MI.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of studies evaluated the relationship between CIMT and presence of atherosclerotic abnormalities in the other territories of the arterial system [ 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. Most studies demonstrated associations between increasing CIMT value and presence and severity of a significant arterial disease (defined as at least 50% or more lumen reduction): CAD, renal artery stenosis, lower and upper extremity athero-oclussive disease, or the abdominal aorta [ 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. However, correlations between CIMT with incidence and severity of lesions in the other arterial sites are modest, especially when only CIMT-CCA is reported [ 78 , 79 , 80 ].…”
Section: Simultaneity Of Atherosclerotic Burden Across Arterial Bedsmentioning
confidence: 99%
“…A recent meta-analysis of 89 studies showed moderate correlation between CIMT and severity of CAD (r = 0.60, p < 0.001) and the number of diseased vessels (r = 0.49, p < 0.001) [ 67 ]. Additionally, carotid plaque presence and calcification were less, and lipid-rich necrotic core was highly prevalent in nonsignificant versus significant CAD ( p < 0.001, p = 0.03, p < 0.001, respectively) [ 67 ]. In another large meta-analysis, including 22 studies, the diagnostic sensitivity and specificity of CIMT for CAD were 0.68 and 0.70, respectively [ 81 ].…”
Section: Simultaneity Of Atherosclerotic Burden Across Arterial Bedsmentioning
confidence: 99%
“…These two artery systems are believed to share similar atherosclerotic phenotypes in plaque formation, luminal narrowing, and arterial wall calcification. 35 Thus, the hub genes identified by analyzing carotid APs may be also linked to the acute manifestation of coronary plaque destabilization. To test this hypothesis, we calculated an APDscore based on the gene expressions of the eight hub genes using GSVA method.…”
Section: Discussionmentioning
confidence: 99%